The Application of the Visual Auditory Kinesthetic Model Assisted by Blooket Media in Teaching News Writing to 11th Grade Students - Amellya Putri Vellysha; Titin Nurhayatin; Aries Setia Nugraha (Journal of Practice Learning and Educational Development, 2025)
This study aims to examine the effectiveness of the Visual Auditory Kinesthetic (VAK) learning model assisted by the Blooket media in improving students’ news writing skills. The research was conducted on eleventh-grade students of SMA Pasundan 3 Bandung using a quasi-experimental method with a non-equivalent control group design. The experimental class was taught using the VAK model and Blooket media, while the control class was taught using conventional discussion methods with PowerPoint. Data were collected through pretest and posttest instruments, as well as observation and documentation. The results showed a significant improvement in the experimental class, where the average posttest score increased to 88.6, compared to the control class which reached only 75.7. The VAK model successfully accommodated students’ diverse learning styles and enhanced their active participation. The use of Blooket, an interactive digital game-based platform, created an engaging and competitive learning environment that supported better understanding and creativity in news writing. This study concludes that the integration of the VAK model with Blooket media is effective in enhancing students’ writing competence, especially in producing structured and factual news texts, in line with 21st-century learning principles that emphasize critical thinking, collaboration, communication, and creativity.